Clinical and economic impact of pharmacist interventions to identify drug-related problems in multidisciplinary cancer care: a prospective trial - Giraud, Jean-Stéphane; Korb-Savoldelli, Virginie; Perrin, Germain; Jouinot, Anne; Sabatier, Brigitte; Batista, Rui; Ribault, Matthieu; De Percin, Sixtine; Villeminey, Clémentine; Videau, Margaux; Blanchet, Benoit; Goldwasser, Francois; et al. (The oncologist (Dayton, Ohio), 2025)
Abstract Background The prescription of antitumor drugs has often been associated with drug-related problems. Pretherapeutic multidisciplinary risk assessment programs including pharmaceutical care have been established to secure the initiation of injectable and oral antitumor therapies. This prospective cross-sectional double-center study evaluated the clinical and economic impact of the pharmacist in detecting drug-related problems in patients initiating antitumor therapies. Materials and Methods Following pharmaceutical consultations, pharmaceutical interventions were validated by a multidisciplinary team. A committee of independent clinical experts assessed the potential clinical impact of drug-drug interactions. The association of clinical variables with pharmaceutical interventions was tested using a multivariate logistic regression model. Pharmacist cost of the program was assessed by valuing pharmacists’ time at their salaries and compared with potentially avoided costs. Results Four hundred thirty-eight patients with solid tumors were included: 62% males, mean age of 65 ± 13 years, and average of 6 medications. Half of the patients required at least one pharmaceutical intervention and independent factors associated with pharmaceutical interventions were the number of medications (5-9 vs <5: OR = 2.91 [95% CI 1.82-4.65], P < .001) and the type of antitumor treatment (immunotherapy vs intravenous chemotherapy: OR = 0.35 [95% CI 0.18-0.68], P = .002). One hundred seventy-four out of 266 pharmaceutical interventions (130 patients) involved clinically significant drug-drug interactions. Pharmacist costs were estimated to range between €4899 and €6125. Average costs were estimated at €11.4-14.3 per patient. Avoided hospitalization costs were estimated to be €180 633. Conclusion Clinical pharmacists contribute to the cost-effective reduction of drug-related problems in pre-therapeutic assessment programs for patients with cancer. Pre-therapeutic multidisciplinary risk assessment programs including pharmaceutical care have been established to secure the initiation of injectable and oral antitumor therapies. This study evaluated the clinical and economic impact of the pharmacist in detecting drug-related problems in patients initiating antitumor therapies. Graphical Abstract Graphical Abstract